Binding Specificity of ASHH2 CW Domain Toward H3K4me1 Ligand Is Coupled to Its Structural Stability Through Its α1-Helix - Bril’kov, Maxim S.; Dobrovolska, Olena; Ødegård-Fougner, Øyvind; Turcu, Diana C.; Strømland, Øyvind; Underhaug, Jarl; Aasland, Rein; Halskau, Øyvind (Frontiers in Molecular Biosciences, 2022)
The CW-domain binds to histone-tail modifications found in different protein families involved in epigenetic regulation and chromatin remodelling. CW-domains recognize the methylation state of the fourth lysine on histone 3, and could therefore be viewed as a reader of epigentic information. The specificity towards different methylation states such as me1, me2 or me3 depends on the particular CW subtype. For example, the CW domain of ASHH2-methyltransferase binds preferentially to H3K4me1, MORC3 binds to both H3K4me2 and me3 modifications, while ZCWPW1 is more specific to H3K4me3. The structural basis for these preferential bindings are not well understood, and recent research suggests that a more complete picture will emerge if dynamical and energetic assessments are included in the analysis of interactions. This study uses fold assessment by NMR in combination with mutagenesis, ITC affinity measurements and thermal denaturation studies to investigate possible couplings between ASHH2 CW selectivity towards H3K4me1 and the stabilization of the domain and loops implicated in binding. Key elements of the binding site – the two tryptophans and the α1-helix form and maintain the binding pocket were perturbed by mutagenesis and investigated. Results show that α1-helix maintains the overall stability of the fold via the I915 and L919 residues, and that correct binding consolidates the loops designated 1, 3, as well as the C-terminal. This consolidation is incomplete for H3K4me3 binding to CW, which experiences a decrease in overall thermal stability upon binding. Moreover, loop-mutations not directly involved in the binding site nonetheless affect the equillibrium positions of key residues.